2015
DOI: 10.1007/s11655-015-2041-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials of integrative medicine for rheumatoid arthritis: Issues and recommendations

Abstract: Controlled clinical trials of integrative therapies available to patients with rheumatoid arthritis (RA) improved dramatically in the past 20 years, largely because of the growing need and the methodologies improvement. Tripterygium wilfordii Hook. F., a typical example of popular use herb, has been extensively studied in trials. However, clear and convincing evidence of integrative therapy, effectiveness and safety, remains insufficient to make decision. Many research efforts are hampered by standing problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this review, authors have concluded that TW extracts are a sort of "herbal DMARD" with a similar efficacy to synthetic DMARDs in RA treatment and that well-designed confirmatory randomized controlled trials should be done (14). Recently, Zhang and co-workers have shown in a multicenter, open-label, randomized controlled trial that combined therapy of methotrexate (MTX) and TW was more effective than MTX monotherapy in the treatment of active RA patients (15, 16). In this study, about 52.7% of the 207 patients experienced adverse events, which were seen in 46.4, 62.3, and 49.3% of patients receiving TW (20 mg, three times per day), MTX (12.5 mg/week), and TW + MTX, respectively ( p  = 0.136).…”
Section: Clinical Experience With the Use Of Twmentioning
confidence: 99%
“…In this review, authors have concluded that TW extracts are a sort of "herbal DMARD" with a similar efficacy to synthetic DMARDs in RA treatment and that well-designed confirmatory randomized controlled trials should be done (14). Recently, Zhang and co-workers have shown in a multicenter, open-label, randomized controlled trial that combined therapy of methotrexate (MTX) and TW was more effective than MTX monotherapy in the treatment of active RA patients (15, 16). In this study, about 52.7% of the 207 patients experienced adverse events, which were seen in 46.4, 62.3, and 49.3% of patients receiving TW (20 mg, three times per day), MTX (12.5 mg/week), and TW + MTX, respectively ( p  = 0.136).…”
Section: Clinical Experience With the Use Of Twmentioning
confidence: 99%
“…Lu, AP broadened the understanding of various factors that can affect the sensitivity of herbal medical interventions by studying the combined effect of different herbs and their interaction with each other. [ 19 ] South Korea has been conducting research on certain pharmacological ingredients extracted from herbs. [ 20 ] This information about the authors, organizations, and countries will contribute to cooperation and communication between researchers across the world.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the most frequent side effects reported in these clinical trials were gastrointestinal disturbances. ( 2 , 3 , 57 – 60 ) More recently, a study has shown that a combination therapy of TW extracts and methotrexate (MTX) is more effective than MTX alone ( 4 , 61 ). This can be a strategy to lower the dose of TW extracts or of celastrol, thus limiting the side effects.…”
Section: Discussionmentioning
confidence: 99%